2021
DOI: 10.1186/s13033-021-00466-y
|View full text |Cite
|
Sign up to set email alerts
|

“We do not know how to screen and provide treatment”: a qualitative study of barriers and enablers of implementing perinatal depression health services in Ethiopia

Abstract: Background Qualitative studies evaluating maternal mental health services are lacking in Ethiopia, and the available evidence targets severe mental illnesses in the general population. We conducted a qualitative study to explore barriers to, enablers of, or opportunities for perinatal depression health services implementations in Ethiopia. Methods We conducted a total of 13 face to face interviews with mental and maternal health service administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 89 publications
2
8
1
Order By: Relevance
“…In a study conducted in Kaduna, Nigeria, only 8.9% was screened which is lower than our finding (26). Qualitative studies conducted on Perinatal depression screening practice in Amhara Regional State, Ethiopia, share common barriers with our study findings: health administrators' low literacy, community awareness, and organizational challenges (38). A qualitative descriptive study done in Victoria, Australia indicated language barrier between professionals and patients also factor influencing screening practice (39).…”
Section: Discussioncontrasting
confidence: 57%
“…In a study conducted in Kaduna, Nigeria, only 8.9% was screened which is lower than our finding (26). Qualitative studies conducted on Perinatal depression screening practice in Amhara Regional State, Ethiopia, share common barriers with our study findings: health administrators' low literacy, community awareness, and organizational challenges (38). A qualitative descriptive study done in Victoria, Australia indicated language barrier between professionals and patients also factor influencing screening practice (39).…”
Section: Discussioncontrasting
confidence: 57%
“…It has been alluded that variations in cultural views on stigma within countries, levels of poverty and access to mental health services, may be contributory factors to these differences [ 91 ]. In some countries including Ethiopia, a mental illness may not be regarded as a life-threatening condition [ 91 , 92 ]. As such, policymakers and planners and health care providers may not prioritised mental health care and treatment [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, Maternal Mental Health Services (MMHS) is seriously lacking within the entire healthcare space due to numerous factors and challenges. Barriers to poor treatment are multifactorial and could be associated with personal behaviour, the severity of the disorder, social norms, and the lack of effective mental health care systems (Dadi et al, 2021). The issue of Maternal Mental Health Services (MMHS) is not deeply rooted in the Ghanaian health sector which is characteristically re ective of how mental health issues are poorly understood and handled in its entirety.…”
Section: Introductionmentioning
confidence: 99%